The Establishment of Sharia-Based Class D General Hospital in Purwantoro Wonogiri - Maryama Aisyah Pribadi (Rumah Sakit Akademik Universitas Gadjah Mada, 2021)
Purwantoro is a very strategic area, located in the middle of its surrounding subdistricts, and is a transit point to get to the surrounding sub-districts. In Wonogiri, there are nine general hospitals, but none are located in Purwantoro. The ratio of hospital beds per 1,000 population in Wonogiri is still 0.96. Indonesia is a country with the largest Muslim population (87.2%). The Muslim population of Wonogiri Regency reached 1,108,696 (97.65%), and specifically in Purwantoro, 99.06% are Muslims. So that awareness and need for sharia-based health services increased. This research is a feasibility study. Primary and secondary data obtained are collected and processed, then analyzed by the situation, demand, and needs, as well as financial analysis. Investment evaluation using the Investible Surplus Method (ISM). Situation analysis, both external and internal aspects, supports this project. Demand and needs analysis also have been fulfilled, but necessary to pay attention to the needs of male nurses. The total cost of the entire project excluding land purchases is Rp 42.231.739.375,00 through two-step constructions with an ISR of 16,81% in the ninth year. The establishment of a sharia-based class D general hospital in Purwantoro Wonogiri is feasible to be established with a capacity of 60 beds at an area of 4.252 m2, an investment value of Rp. 42.231.739.375,00 through two-step constructions with ISR of 16,81 % for nine years.